Analytical prediction model for circular SMA-confined reinforced concrete columns. (15th June 2020) - Abdelrahman, Khaled; El-Hacha, Raafat
Highlights: Development of analytical model to predict concentric response of shape memory alloy confined reinforced concrete columns. Design procedure developed to utilize proposed model for design aid purposes. Model accurately predicts maximum strength and ultimate strain values compared with values observed experimentally. Model captures overall curvilinear stress-strain response as demonstrated by tested specimens. Abstract: Several confinement methods using concrete casing, steel jacketing, and wrapping with Fibre Reinforced Polymer (FRP) sheets are widely implemented to enhance the strength and ductility of reinforced concrete (RC) columns. Recently, smart materials such as Shape Memory Alloys (SMA) are utilized for repair and strengthening of RC columns. The SMA's exhibit unique thermo-mechanical properties such as shape memory effect (SME) that enables the material to achieve high recovery stress (up to 600 MPa) and strain (up to 8%). Recent findings in the literature show the SME and high recovery stress of the SMA wires used to confine concrete columns significantly enhanced the strength and ductility performance of concrete. Realizing the potential of the SMA-confinement technique, this paper aims to present an analytical model to describe the behaviour of SMA-confined RC columns subjected to uni-axial compressive loads. Experimental data are compared against theoretically predicted results to validate the proposed analytical model. Results show the proposed analytical model predictions are in good agreement with the experimentally observed axial compressive response of SMA-confined RC columns.